Crosstalk of kidney and brain in diabetes-related cognitive impairment and therapeutic strategies - Xu, Chunmei; Miao, Huikai; Chen, Yongjun; Liao, Lin (Frontiers in Endocrinology, 2025)
Type 2 diabetes mellitus (T2DM) and its associated complications pose a global health threat. Notably, the rise in diabetes-induced cognitive dysfunction has garnered widespread attention. T2DM patients frequently face an elevated risk of both cognitive impairment and diabetic kidney disease (DKD) comorbidity. There is evidence to suggest that kidney and brain dysfunction share common pathogenic factors, such as vascular endothelial injury, oxidative stress, and inflammation activation. Whereas, the underlying mechanisms of kidney-brain interaction and effective treatments for DKD-related cognitive decline remain incompletely understood. Our review preliminarily summarized the relationship between renal dysfunction and cognitive decline based on the existing clinical trial evidence. The mechanisms underlying DKD-related cognitive decline which mainly included the accumulation of harmful metabolites, inflammation activation and endothelial dysfunction were also clarified. And the brain renin-angiotensin-aldosterone system (RAAS) may serve as a bridge connecting renal dysfunction in DKD with cognitive impairment. In addition, we further concluded that potential lifestyle interventions and pharmacological approaches, including antioxidants, RAS inhibitors, finerenone and hypoglycemic agents, such as sodium-glucose cotransporter-2 inhibitors, liraglutide and pioglitazone may exert the preservation of cognitive function. The review could offer valuable insights for therapeutic strategies of cognitive impairment associated with diabetes and DKD in future.